Expanding reimbursement of immediate treatment using direct acting antivirals to reduce hepatitis C incidence among HIV positive men who have sex with men in Bangkok, Thailand: A cost effectiveness modelling study - Shreoshee Mukherjee; Donn Colby; Reshmie Ramautarsing; Stephanie Popping; Somchai Sriplienchan; Tanat Chinbunchorn; Nittaya Phanuphak; David van de Vijver (Elsevier, 2021)
Background: Increasing number of hepatitis C virus (HCV) infections among HIV positive men whohave sex with men (MSM) as in an acute HIV infection cohort study in Bangkok, reached an incidence of 45/1000 person-years in 2018. Direct-acting antivirals (DAAs), that cure HCV infection and thereby can prevent transmission, are expensive, their reimbursement being presently delayed to the chronic stages of liver fibrosis. The aim of this study was to determine the cost-effectiveness of immediate DAA treatment to reduce HCV transmission among HIV positive MSM in Bangkok. Methods: A deterministic transmission model was calibrated to the HCV epidemic among HIV positive MSM in Bangkok. We compared the current practice of starting DAAs at METAVIR stage F2 rather than at stage F1, or immediately after diagnosis, at stage F0. Cost-effectiveness was examined from a payer's perspective, using a 3% annual discounting rate. Results: Compared to the incidence in 2018, delaying DAA treatment to METAVIR stage F2 or F1, increases HCV incidence in 2030 to 63/1000 person-years and 56/1000 person-years, respectively. Conversely, immediate DAA treatment reduces the incidence to 26/1000 person-years. Compared to initiating treatment at stage F2, immediate treatment is cost saving within seven years and saves $17 million over 40 years. One-way sensitivity analysis showed that lower cost savings were achieved at a higher price of DAA treatment and at less frequent HCV screening. Conclusion: Immediate DAA treatment is cost saving and increases health benefits by reducing HCV incidence among HIV-infected MSM.